Red Blood Cell Deformability, Age, Ethnicity and Susceptibility to Malaria in Africa - Henry, Benoît; Roussel, Camille; Ndour, Papa Alioune; Carucci, Mario; Duez, Julien; Fricot, Aurélie; Aussenac, Florentin; Akpovi, Hilaire; Courtin, David; Clain, Jérôme; Colin Aronovicz, Yves; Garcia, André; et al. (Blood, 2016)
Introduction: malaria is one of the most frequent hematological diseases worldwide. Because the malaria parasite Plasmodium falciparum develops mainly in red blood cells (RBC), splenic retention of infected and uninfected RBC is likely a key player in the variable susceptibility of humans to malaria. Age and ethnicity are important determinants of the manifestations of malaria in Africa (Reyburn JAMA 2005, Dolo Am J Trop Med Hyg 2005; Greenwood Ann Trop Med Parasitol 1987; Torcia PNAS 2008), Asia (Price Am J Trop Med Hyg 2001), and in travelers (Seringe Emerg Infect Dis 2011). We had speculated that variations in the splenic sensing of RBC contribute to the innate protection/susceptibility of infants against distinct forms of severe malaria and to the pathogenesis of chronic malaria (Buffet Curr Opin Hematol 2009; Buffet Blood 2011). Here, we explore the deformability and morphology of circulating RBC in populations living in a malaria-endemic area. Materials and methods: experiments were embedded in an integrated study driven by Institut de Recherche pour le Développement, which aims at the identification of genetic, epidemiologic and anthropologic determinants of susceptibility to malaria. IRB approval was obtained from Institut des Sciences Biomédicales Appliquées, Benin. Clinical and biological data were collected at the beginning of the rainy season from 627 individuals, belonging to 4 different ethnic groups living in sympatry in Atakora, North Benin and included age, gender, ethnicity, body temperature, presence and grade of splenomegaly, rapid diagnostic test for malaria (RDT), thick film and rapid hemoglobin determination with HemoCue©. Venous blood was collected for determination of RBC morphology and deformability. Using microsphiltration, a RBC filtering method that uses microsphere layers to mimic the mechanical retention of RBC in the splenic red pulp (Deplaine Blood 2011) we quantified the ability of a mix of labeled and non-labeled RBCs to squeeze between calibrated slits, results being expressed as retention or enrichment rates (RER) of subject’s RBC compared to normal RBC (from a single French O-positive donor) stored in blood bank conditions. Microsphiltration has been adapted to high-throughput experimentation using microplates (Duez AAC 2015). Experiments were performed in a field laboratory established on site; microplates were prepared in Paris and brought to North Benin in luggage with constant care to avoid shocks during transportation. All RBC samples were filtered in triplicate less than 8 hours after blood collection. Up- and downstream samples were brought back to France at 4°C in sealed micro-well plates and analyzed for individual RER calculation in the next 2 weeks by flow cytometry. Results: over 10 days, 262 adults and 249 children were included, 31% Bariba, 17% Gando (genetically related to Bariba), 24% Otamari, 27% Peulhs. Prevalences of splenomegaly, positive RDT, and fever were 13%, 27%, and 2%, respectively. Of 629 blood samples collected, 511 could be analyzed. RER of controls remained stable with time and across 17 microfiltering plates, with a median (IQR) retention rate of 12% (5% - 21%). Ethnicity and age were the only two factors associated with statistically significant differences in RER (figures 1 and 2). Infants (less than 2 year-old) had a more important enrichment than older children and adults (median in 2 years old or less 287%; 3 to 5 years 103%; 6 to 10 years: 64%; more than ten years: 91%; p=0.0161). Peulhs and Otamari also had higher median enrichment rates than Bariba and Gando (RER: 122% and 118%, 75%, 64%, respectively; p=0.0246). Conversely, splenomegaly, gender, positivity of RDT or anemia at the time of sampling were not associated with RER. Discussion: higher averaged enrichment rates in specific ethnic subgroups, namely Peulhs and Otamari, likely result from a more stringent splenic retention, leaving more deformable RBC in circulation. An innate spleen-RBC interaction process was also observed in infants, which is consistent with the higher incidence of severe malarial anemia and splenomegaly observed in this population (Reyburn JAMA 2005; Price Am J Trop Med Hyg 2001). Our results show that innate factors (e.g. ethnicity and age) tend to influence the deformability of RBC, and therefore the phenotypic expression of malaria in Africa. Ongoing experiments aim at deciphering the mechanisms responsible for these differences. [Display omitted] [Display omitted] No relevant conflicts of interest to declare.